Boundary crossing: an experimental study of individual perceptions toward AIGC - Tao, Wei; Gao, Shuang; Yuan, Yilang (Frontiers in Psychology, 2023)
Artificial Intelligence (AI) Generated Content has made great progress in many fields. Those AI art works gradually reshape contemporary understanding of creativity. The unique creative ability of human beings may also be challenged. This paper takes AIGC as the research object and carries out a grouping experiment based on 240 participants. We found that Anthropomorphism and Autonomy have no effect on the evaluation of AI paintings and AI “painter” identity, but in together their have a combined positive impact on both independent variables. The existence of moderating effect reveals the phenomenon of on-the-spot stimulation similar to the strong effect theory. Meanwhile, the evaluation of paintings positively affects the perception of AI “painter” identity. The subjectivity of AI comes from the double superposition of its external and inner characteristics, which may suggest AI with both human-like appearance and function can be regarded as a person with social role identity.